Influence of Cervitec gel on periodontal health of patients wearing fixed orthodontic appliances - Burcu Özdemir; Ahu Uraz; Duygu İşcan; Şeyma Bozkurt; Burcu Baloş Tuncer; Doruk Engin; Selcen Pehlivan; Hakan İşcan (Elsevier, 2014)
Background/purpose: This double-blinded randomized placebo-controlled study aimed to evaluate the efficacy of 0.2% chlorhexidine containing Cervitec gel on periodontal health during orthodontic treatment. Materials and methods: Twenty-five patients undergoing fixed orthodontic treatment were randomly assigned to the Cervitec (n = 13) or control (n = 12) groups. After clinical examination at first visit, all patients received professional prophylaxis, and 2 weeks later baseline (B) evaluations are performed. Later, oral hygiene procedures were refrained for 3 days until Day 0, during which the participants in the Cervitec group were instructed to brush with standard toothpaste (ST) (1 × 1) and Cervitec (1 × 1), whereas the control group received placebo (1 × 1) until Day 14. Between Day 14 and Day 28, patients returned to brushing with ST (2 × 1). The clinical measurements were recorded and subgingival plaque samples were collected at first visit, B, Day 0, Day 14, and Day 28. Subgingival plaque samples were analyzed for total bacteria, Porphyromonas gingivalis (P.g.), and Treponema denticola (T.d.) using real-time polymerase chain reaction. The data were statistically analyzed. Results: After receiving professional prophylaxis and oral hygiene instructions, remarkable improvements was seen in clinical and microbiological variables of the study. Although there was a significant reduction in the Quigley-Hein Plaque Index (mQHI) score at Day 14 in only the Cervitec group (P < 0.01), both the Cervitec group and the control group revealed significant reductions in the mQHI score at Day 28 compared with Day 0 (P < 0.001 and P < 0.01, respectively). Intragroup and intergroup evaluations revealed no statistically significant alterations for P.g. and T.d. Conclusion: The present data suggested that brushing with Cervitec gel once a day has the potential to reduce bacterial accumulation around teeth and fixed appliances in patients undergoing orthodontic treatment. However, within the limits of this study, Cervitec seems to have no significant effect on total bacteria, P.g., and T.d. levels of subgingival dental plaque.